Dor dental: determinantes e impactos em escolares do sul do Brasil - Schuch, Helena Silveira (2014)
Despite the decline observed in the occurrence of oral problems, studies among schoolchildren has revealed that dental pain is still a problem of high prevalence, and may have a negative impact on quality of life of individuals and society. Considering the relevance of the topic and that there are few epidemiological studies that assess the phenomenon of pain, this cross-sectional study aimed to evaluate the report of dental pain in a school-based sample of children in South Brazil and test the association with socioeconomics, demographic, psychosocial and clinical variables. Also, aimed to investigate the consequences of dental pain on oral health perception and impact on children s daily life. A minimum sample size of 922 children was estimated. The sample, random and stratified, was selected by multistage sampling technique and evaluated in 20 schools, located in Pelotas/RS in 2011. Data collection consisted of a questionnaire to parents to obtain socioeconomic features; of interview with children, including information on family structure, on the occurrence of dental pain in the last month and in the last six months preceding the interview, on dental fear and about the perception of their oral health; and of oral clinical examination of children, who were assessed for dental caries, dental trauma and malocclusion. Data were entered twice in an EpiData 3.1 database and analyses were performed in Stata 12.0. Descriptive analysis was performed to obtain the prevalence of the dependent variable. Then, bivariate analyses were performed to test the association between dental pain and independent variables. To investigate the independent effect of variables on dental pain occurrence, Poisson regression analysis was performed, estimating the Prevalence Ratio (PR) and respective confidence intervals (95% CI). 1,199 children aged 8-12 was included in the sample. A higher prevalence of dental pain was observed in children from lower income families (PR=1.39; 95%CI 1.10-1.76), in girls (PR=1.24; 95%CI 1.06-1.46), living in overcrowded houses (PR 1.23; 95%CI 1.01-1.49), who reported dental fear (PR=1.19; 95%CI 1.00-1.42), and in children with caries experience (PR=1.57; 95%CI 1.34-1.84), after adjustments. Dental pain presence influenced in oral health perception PR=2.56; 95%CI 1.55-3.29) impacted in children s daily life (PR=1.89; 95%CI 1.64-2.17). Conclusion: A high percentage of schoolchildren suffered from dental pain, which was influenced by demographic, socioeconomics, psychosocial and clinical characteristics, causing negative impact on the oral health perception